2014
DOI: 10.1063/1.4866647
|View full text |Cite
|
Sign up to set email alerts
|

A fast microchannel plate-scintillator detector for velocity map imaging and imaging mass spectrometry

Abstract: The time resolution achievable using standard position-sensitive ion detectors, consisting of a chevron pair of microchannel plates coupled to a phosphor screen, is primarily limited by the emission lifetime of the phosphor, around 70 ns for the most commonly used P47 phosphor. We demonstrate that poly-para-phenylene laser dyes may be employed extremely effectively as scintillators, exhibiting higher brightness and much shorter decay lifetimes than P47. We provide an extensive characterisation of the propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 40 publications
0
30
0
Order By: Relevance
“…A bright flash on a scintillating screen will trigger a large cluster of pixels, with a short response time, giving a more reliable signal. To this end, more efficient scintillators, such as those proposed by Brouard and co‐workers, should improve the performance of the PImMS sensor . The response time of the BC‐408 scintillator used here is short enough (2.5 ns) that it should not affect the time resolution for ion detection but when further planned firmware improvements reduce the PImMS timing precision to 6.25 ns, there will be a demand for still faster scintillators.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A bright flash on a scintillating screen will trigger a large cluster of pixels, with a short response time, giving a more reliable signal. To this end, more efficient scintillators, such as those proposed by Brouard and co‐workers, should improve the performance of the PImMS sensor . The response time of the BC‐408 scintillator used here is short enough (2.5 ns) that it should not affect the time resolution for ion detection but when further planned firmware improvements reduce the PImMS timing precision to 6.25 ns, there will be a demand for still faster scintillators.…”
Section: Discussionmentioning
confidence: 99%
“…To this end, more efficient scintillators, such as those proposed by Brouard and co-workers, should improve the performance of the PImMS sensor. [49] The response time of the BC-408 scintillator used here is short enough (2.5 ns) that it should not affect the time resolution for ion detection but when further planned firmware improvements reduce the PImMS timing precision to 6.25 ns, there will be a demand for still faster scintillators. In conclusion, we have shown that the PImMS camera, in combination with an off-the-shelf mass spectrometer, is capable of multi mass imaging with mass resolutions greater than the isotopic limit Δm 50 % = 1 m/z unit over a range of 200 ≤ m/z ≤ 800, while still achieving an optimum spatial resolution of 25 μm.…”
Section: Discussionmentioning
confidence: 99%
“…The response time of this arrangement is 3.7 ns. 29 Flashes of light corresponding to individual ion events are then recorded simultaneously using an intensified CCD camera and a photomultiplier tube (PMT) or with an event-triggered fast imaging sensor. [30][31][32] The ion optical assembly comprises five cylindrical electrodes: a repeller, an extractor, and an einzel lens.…”
Section: Article Scitationorg/journal/rsimentioning
confidence: 99%
“…In both cases, ions were detected using a pair of stacked 25 mm microchannel plates (Photonis) coupled with a home-built Exalite 404 scintillator [36]. When compared to typical P47 screens, Exalite 404 scintillators have a faster response time, which allows the mass resolution of the instrument to be more accurately determined.…”
mentioning
confidence: 99%